Concurrent activity of anammox and denitrifying bacteria in the Black Sea - Kirkpatrick, John B.; Fuchsman, Clara A.; Yakushev, Evgeniy; Staley, James T.; Murray, James W. (Frontiers in Microbiology, 2012)
After the discovery of ANaerobic AMMonium OXidation (anammox) in the environment, the role of heterotrophic denitrification as the main marine pathway for fixed N loss has been questioned. A 3 part, 15 month time series investigating nitrite reductase (nirS) mRNA transcripts at a single location in the Black Sea was conducted in order to better understand the activity of anammox and denitrifying bacteria. Here we show that both of these groups were active, as well as being concurrent in the lower suboxic zone over this time span. Their distributions, however, differed in that only expression of denitrification-type nirS was seen in the upper suboxic zone, where geochemistry was variable. Depth profiles covering the suboxic zone showed that the four groups of anammox-type sequences were expressed consistently in the lower suboxic zone, and were consistent with anammox 16 S rDNA gene profiles. By contrast, denitrifier-type nirS sequence groups were mixed; some groups exhibited consistent expression in the lower suboxic zone, while others appeared less consistent. Co-occurrence of both anammox and denitrifier expression was common and ongoing. Both types of transcripts were also found in samples with low concentrations of sulfide (>2 μM). Six major groups of denitrifier-type nirS transcripts were identified, and several groups of denitrifier-type nirS transcripts were closely related to sequences from the Baltic Sea. An increase in denitrifier-type nirS transcript diversity and depth range in October 2007 corresponded to a small increase in mixed layer net community productivity (NCP) as measured by O2/Ar gas ratios, as well as to an increase in N2 concentrations in the suboxic zone. Taken together, the variations in expression patterns between anammox and denitrification provide one possible explanation as to how near instantaneous rate measurements, such as isotope spike experiments, may regularly detect anammox activity but underreport denitrification.